Imperfect Information, Uncertainty, and Credit Rationing: A Reply - Jaffee, Dwight M.; Russell, Thomas (Quarterly Journal of Economics, 1984)
Dwight M. Jaffee, Thomas Russell; Imperfect Information, Uncertainty, and Credit Rationing: A Reply*, The Quarterly Journal of Economics, Volume 99, Issue 4, 1